Pandangan Masyarakat Jepang Terhadap Sikap Berbahasa - Rudy Setiawan Makmur (Jurnal Pustaka Nusantara dan Budaya, 2013)
The purpose of this study is to clarify Japanese people perspective towards language attitudes and how Japanese people maintain the Japanese language as an expression of nationalism. To see how the Japanese people perspective towards language attitudes the author uses the theory of “Konsistensi Afektif-Kognitif Rosenberg”. All of the data was obtained through library research methods and searching through the internet. After doing the research the author found that the Japanese people maintain their language through a variety of ways. Start from arranging the curriculum by the government, dubbing all the foreign films into Japanese language, and use their language with carefully. The conclusion of this research is that the Japanese government arranging the curriculum to make the student learn more Japanese rather than English, the reason Japan dub foreign movie is to hide the elements of other countries which contained in that movie, and lastly that actually it’s not that the Japanese people can’t speak English, they just didn’t have enough courage to speak in English.